Sources of Revenue for the European Union Budget - Current State, Weaknesses and Proposed Solutions - Kaczyńska , Aneta (Studia Oeconomica Posnaniensia, 2014)
For many years numerous weaknesses have been suggested in the literature regarding the current legal regulations concerning the sources of revenue of the European Union budget. The need for reforming the revenue system of the EU budget has been indicated since the beginning of the 21st century; however, due to the longer than originally expected ratification process for the Lisbon Treaty and the global financial crisis, a solution to this problem is constantly being postponed. The aim of this article is to present the proposed new arrangements of this system, with particular emphasis on the concept of new own resources based on value added tax (VAT). In order to verify that the revenue of the EU budget from new own resources based on VAT will be characterized by relative stability, the correlation between VAT revenue and the gross domestic product (GDP) of the Member States was examined using Spearman’s rank correlation coefficient. It turned out that these variables are strongly positively correlated. Therefore, it can be assumed that the revenue of the EU budget from new VAT-based own resources will be characterized by mediumterm volatility caused by cyclical fluctuations of the EU economy and the national economies of the Member States. Hence, it is concluded that the reformed revenue system of the EU budget should continue to include the own resources based on gross national income (GNI), since these resources make it possible to balance the revenue and expenditure of the EU budget in each year.